Oregon EMS Psychomotor Skills Lab Manual - Hamper, Chris; Curtz, Carmen; Kennel, Jamie; Edwins, Holly (Open textbook library., 2023)
Emergency Medical Technicians (EMTs) must be prepared for an array of possible emergencies while on duty. These skills must be ingrained through practice to withstand the stress of an emergency scene: ready at a moment’s notice, should the patient condition necessitate. Within this book you will find many of the skills an EMT will be expected to perform. Each student is required to complete each skill a minimum number of times. This effort will assist the instructional team in tracking your progress, as well as provide you with the documentation necessary to prove proficiency for national and state certification. The skills in this text are important to master but remember, a truly proficient EMT is refreshing old skills and acquiring new ones throughout their career.